Character’s Attitudes toward the Environment in the Novel Bara by Febrialdi R.: Literary Ecological Study (International Journal of Scientific Research and Management (IJSRM), 2024)
Character attitudes towards the environment are often found in the novel Bara by Febrialdi R. This research aimed to determine the form of natural ecology and cultural ecology in the novel Bara by Febrialdi R. The data source for this research is the novel Bara by Febrialdi R. with the number 372 pages published in 2017 by Mediakita containing the attitudes of figures towards the environment. This research used the listening method and using note-taking techniques. Listening is done by listening to all the speech directly and recording the speech which contains the character’s attitude towards the environment purposively. The research results show that the characters’ attitudes towards the environment in this novel consist of two forms, namely natural ecology and cultural ecology. Furthermore, natural ecology consists of two forms, namely a respectful attitude towards nature and living simply and in harmony with nature, moreover, cultural ecology consists of six forms, namely beliefs, values, norms and sanctions, technology, symbols and language.